Justice, Social Order and the Predicament of the Common Man in Nigeria: Perspectives in Contemporary African Studies - Obinyan, Valentine Ehichioya; Onobhayedo, Albert (NIU Journal of Humanities, 2024)
African studies, in contemporary times, have paid significant attention to the place and value of the individual and the structures or institutions of the society where justice play a very definite role. Justice has to do with respect for the right of the individuals or every member of the society. This is because the tendency of the basic structures and principles of today’s society to reduce the individuals to an instrument is very high. The rights of the human person are inalienable hence are present at birth and continue throughout life.  Is this recognized by every society and their leadership? Have class structures not relegated the right of some individuals to the background? Is there justice for the common man in Nigeria? The problem at hand now is can we formulate, modify and justify a set of principles, structures and standards that could guarantee equity, fairness, justice and ultimately, social order in society? Understanding this problem is one of the purposes of this study. To ensure this, the study adopts the phenomenological and critical analysis methods and argues for effective and efficient distribution of justice; such that will ensure social order and value for human life as well as dignity for the human person in all the classes of the society in Nigeria and Africa especially the class of the common man. Keywords: Justice, Social Order, Common man, Africa, Nigeria, African Philosophy, Egalitarianism, Classism, Human Value, Leadership